2018
DOI: 10.1021/acs.est.8b00094
|View full text |Cite
|
Sign up to set email alerts
|

PPCP Degradation by Chlorine–UV Processes in Ammoniacal Water: New Reaction Insights, Kinetic Modeling, and DBP Formation

Abstract: The combination of chlorine and UV (i.e., chlorine-UV process) has been attracting more attention in recent years due to its ready incorporation into existing water treatment facilities to remove PPCPs. However, limited information is available on the impact of total ammonia nitrogen (TAN). This study investigated two model PPCPs, N,N-diethyl-3-toluamide (DEET) and caffeine (CAF), in the two stages of the chlorine-UV process (i.e., chlorination and UV/chlor(am)ine) to elucidate the impact of TAN. During chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Meanwhile, UV/H 2 O 2 and UV/ClO 2 induced only tiny amounts of I-THMs, which might owe to the reactions between different radicals and iodine species in these systems [63,64]. In UV/H 2 O 2 , both H 2 O 2 and % OH can react with I − (reactions ( 22)-( 26)) [79,87], hence almost no I-THMs were detected in subsequent chlorination and chloramination (F 1 and F 2 in Fig.…”
Section: Dbps-related Toxicity Evaluation In Sequential Disinfection Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, UV/H 2 O 2 and UV/ClO 2 induced only tiny amounts of I-THMs, which might owe to the reactions between different radicals and iodine species in these systems [63,64]. In UV/H 2 O 2 , both H 2 O 2 and % OH can react with I − (reactions ( 22)-( 26)) [79,87], hence almost no I-THMs were detected in subsequent chlorination and chloramination (F 1 and F 2 in Fig.…”
Section: Dbps-related Toxicity Evaluation In Sequential Disinfection Processesmentioning
confidence: 98%
“…However, the relevant rate growth slowed down obviously. This could be attributed to the transformation of primary radicals to nitrogen-containing radicals (NH 2 % and NHCl%, etc), which was considered to have lower oxidative capacity and could be ignored in the degradation of iopamidol (reactions (2), (5) (10) and (12) in Table S3) [23,30,63]. Moreover, chloramines could also eliminate %OH and the reaction was more easily to occur than that between %OH and HClO (reactions (5) and (12) in Table S3) [30,64].…”
Section: Degradation Of Iopamidol By Uv/nh 2 CL Processmentioning
confidence: 99%
“…Studies have shown that the combination of UV and chlorination (UV/chlorine) is more effective in degrading micropollutants than UV or chlorination alone (Cheng et al, 2018;Zhang et al, 2018). Studies on micropollutants included hormones, pharmaceuticals, taste and odor compounds (Ting and Praveena, 2017;Fang et al, 2018;Chang et al, 2019).…”
Section: Uv/chlorinationmentioning
confidence: 99%
“…Ingesting water containing ARB and ARGs may likely alter the intestinal microbiota and this may lead to the proliferation of harmful pathogens in the human body and hence various diseases ranging from stomach disorder to colorectal cancer [9]. Therefore, the complete removal of ARB and their associated genes from food and the environment is now of global importance [10] with coalition of countries coming together to fight it such as the Joint Programming Initiatives on Antimicrobial Resistance (JPIAMR) https://www.jpiamr.eu/ Several attempts have been made to remove ARB and their associated genes from water: membrane technologies [11] advanced biological treatment [12] and various types of advanced oxidation processes including the use of UV-Chlorine [13], UV/H2O2 [14], UV-C [15], Solar water disinfection (SODIS) [16], Fe-doped ZnO nanoparticles, TiO2 nanoparticles doped with cobalt and silver [17,18], TiO2-rGO [19], chitosan modified hybrid clay [20] and bacteriostatic clay [21]. The use of photocatalyst for water disinfection is gaining attention because of the ability of most photocatalyst to mineralise (photodegrade to CO2 and H2O) the bacteria in water.…”
Section: Introductionmentioning
confidence: 99%